PEMAKNAAN DALAM PUISI “BUKAN BETA BIJAK BERPERI” KARYA RUSTAM EFFENDI DENGAN MENGGUNAKAN PENDEKATAN HERMENEUTIKA - Dina Siti Patimah Dewi; Dewi Irma Rimadona; Dadan Firmansyah (Concept: Journal of Social Humanities and Education, 2022)
Analyzing a literary work can be done in a wide variety of ways or approaches. This article discusses the hidden meaning of the poem by Rustam Effendi. This discussion aims to better understand the reader of the content of the poem. The theory used in this refrain is Zygmunt Bauman's Heurmenetic theory which focuses on the clarity of the message and the basic understanding of an obscure speech or writing. The method used in this analysis is a qualitative descriptive method where this research is carried out to examine an object with natural characteristics to create factual research results. The stages carried out in this discussion begin with analyzing the array, analyzing the structure that composes the text of the poem, objectifying the structure of the text, and interpreting the text of the poem. Thus, the results of this study can show the hidden meaning in the poem "Not Beta Bijak Berperi" by Rustam Effendi as a form of ideology that the poet uses in representing ideas in the form of poetry.